Exploring slum children's life- world - Mohapatra, Samapika (Delhi Serials Publications, 2012)
Study conducted in Bhubaneswar, Orissa, India.
Folded map tipped in
Originally presented as the author$1 (Bs thesis (Ph. D.)--Jawaharlal Nehru University.s
Includes bibliographical references (p. [241]-256).
Keywords: Poor children -- India -- Bhubaneswar -- Social conditions; Poor children -- Education -- India -- Bhubaneswar; Slums -- India -- Bhubaneswar